IMPLEMENTASI ASESMEN BERDIFERENSIASI SEBAGAI UPAYA PERWUJUDKAN PENDIDIKAN BERKUALITAS PADA SEKOLAH INKLUSI DI KOTA MALANG - Farizza, Rifqi Al; Waliah, Diyah Rutin; Arifin, Slamet; Ekawati, Ratna (STKIP Persada Khatulistiwa Sintang, 2026)
This study examines inclusive assessment as a fundamental paradigm shift grounded in the principles of equity and equal opportunity. It emphasizes recognizing and valuing student diversity, particularly the unique potential of students with special needs, rather than measuring conformity to a single standard. The implementation of formal assessment in inclusive schools requires extensive modifications and accommodations. Common accommodations include extended time and adjustments to assessment formats, such as large-print texts and illustrated questions. These are based on individual assessments and aligned with Individualized Education Programs (IEPs). In practice, most educators modify the content and format of standard assessments to ensure pedagogical fairness and provide equal opportunities for students to demonstrate their competencies. Beyond evaluation, modified assessment serves as a crucial diagnostic tool. It helps identify students’ learning needs, facilitates targeted interventions, and contributes to improved learning outcomes and self-confidence among students with special needs. Although its effectiveness depends on consistency, collaboration, and data-driven observation, modified assessment represents a meaningful commitment to valuing each student’s learning process and unique potential in inclusive education.